1999
DOI: 10.1021/bi982707s
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the Proximal Histidine Iron Ligand by a Cysteine or Tyrosine Converts Heme Oxygenase to an Oxidase

Abstract: The H25C and H25Y mutants of human heme oxygenase-1 (hHO-1), in which the proximal iron ligand is replaced by a cysteine or tyrosine, have been expressed and characterized. Resonance Raman studies indicate that the ferric heme complexes of these proteins, like the complex of the H25A mutant but unlike that of the wild type, are 5-coordinate high-spin. Labeling of the iron with 54Fe confirms that the proximal ligand in the ferric H25C protein is a cysteine thiolate. Resonance-enhanced tyrosinate modes in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
111
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 53 publications
16
111
3
Order By: Relevance
“…This midpoint potential value agreed closely with those reported previously, i.e. −0.076 V vs NHE for heme-rHO-1 complex [30] and −0.065 V vs NHE for heme-human HO-1 complex [31] (Table 1). The slope of the Nernst plot, ~0.084, indicated that this process is a one-electron oxidation of ferrous heme.…”
Section: Electrochemical Titration Of Heme-rho-1 Complex Under Anaerosupporting
confidence: 92%
“…This midpoint potential value agreed closely with those reported previously, i.e. −0.076 V vs NHE for heme-rHO-1 complex [30] and −0.065 V vs NHE for heme-human HO-1 complex [31] (Table 1). The slope of the Nernst plot, ~0.084, indicated that this process is a one-electron oxidation of ferrous heme.…”
Section: Electrochemical Titration Of Heme-rho-1 Complex Under Anaerosupporting
confidence: 92%
“…These frequencies are characteristic of a 5-coordinate high-spin ferric heme (23). In porphyrins bound to a proximal histidine, the ν 4 mode dominates the high-frequency spectra, but in Dap1p, as in other hemoproteins lacking a proximal histidine, the ν 4 and ν 3 modes have comparable intensities (24,25). Attempts to confirm the iron(III) ligation to a tyrosine with RR experiments using a 514.5-nm excitation were inconclusive (data not shown).…”
Section: Rr Characterization Of Dap1pmentioning
confidence: 97%
“…The frequencies of the phenolate modes observed for a number of heme iron-tyrosinate proteins are listed in Table 1 [20,[29][30][31][32][33][34]. In general, ferric-heme proteins with tyrosinate ligation have been found to have penta-or hexa-HS heme states.…”
Section: Spectroscopy At Room Temperaturementioning
confidence: 99%